KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS KECAMATAN KEBAYORAN LAMA JAKARTA SELATAN - Tri Widyastuti,, Fitta; Subowo, Ari; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Quality Health Services is something that is important for the entire community to obtain. This study aims to analyze the quality of health services and factors related to the quality of services at the Kebayoran Lama District Health Center with a research focus on UKP (Individual Health Enterprise) services. The research method used was a qualitative method with a descriptive type, data was obtained through observation, interviews and literature study, and used an informant selection technique, namely purposive sampling. To test the validity of the data using triangulation, the research results show that in the quality theory used there are four significant symptoms, namely tangibles, reliability, responsiveness, assurance, and one less significant symptom, namely empathy. Then in the second objective theory, namely factors related to service quality, there are five significant symptoms and 1 less significant symptom. There are findings that can be used as a way to improve and maintain the quality of health services at the Kebayoran Lama District Health Center, South Jakarta, such as the implementation of hospitality which is currently underway.